«Dir lo latí en so de romanç» - Nadal, Josep M. (Caplletra. Revista Internacional de Filologia, 2015)
The author discusses the relationship between the two techniques of Medieval translation, the loss of Latin as the only written model and the creation of a literary language in Vulgar Latin in the 14th and 15th centuries.